Evaluating imaging and computer-aided detection and diagnosis devices at the FDA. - Gallas BD; Chan HP; D'Orsi CJ; Dodd LE; Giger ML; Gur D; Krupinski EA; Metz CE; Myers KJ; Obuchowski NA; Sahiner B; Toledano AY; et al. (Academic Radiology, 2012)
This report summarizes the Joint FDA-MIPS Workshop on Methods for the Evaluation of Imaging and Computer-Assist Devices. The purpose of the workshop was to gather information on the current state of the science and facilitate consensus development on statistical methods and study designs for the evaluation of imaging devices to support US Food and Drug Administration submissions. Additionally, participants expected to identify gaps in knowledge and unmet needs that should be addressed in future research. This summary is intended to document the topics that were discussed at the meeting and disseminate the lessons that have been learned through past studies of imaging and computer-aided detection and diagnosis device performance.